Histopathology and virulence of an in vitro-adapted Trypanosoma evansi TEDC 953 strain (Thailand isolate) in mice - Wallaya Phongphaew; Charuwan Wongsali; Thanisorn Boonyakong; Theerawat Samritwatchasai; Wissanuwat Chimnoi; Ketsarin Kamyingkird (Veterinary World, 2023)
Background and Aim: Trypanosoma evansi is a blood and tissue protozoan parasite affecting domestic and wild animals. The T. evansi Thai strain, namely, T. evansi from dairy cattle number 953 (TEDC 953) strain, has been successfully isolated from dairy cattle and cultivated in vitro. The in vitro-cultivated parasite is useful for biological studies, evaluation of novel chemotherapeutic agents, and production of antigens for diagnostic tests. This study aimed to observe the histopathology and virulence of an in vitro-adapted T. evansi TEDC 953 strain in vivo.